THE IMPORTANCE OF GAMES IN TEACHING - Alimova Madinabonu Islomjon qizi (Scholars Digest Publishing, 2023)
Gaming has been a part of human tradition for centuries, imparting amusement and social interaction. But its significance is going past mere amusement . Games have confirmed to be powerful academic tools, specifically withinside the region of language learning. It gives a a laugh and attractive manner to study new concepts, fortify present knowledge, and increase crucial competencies together with trouble fixing and communication. This article explores the blessings of the usage of video games withinside the school room and why video games need to now no longer be omitted as treasured academic tools.
Keywords: learning games, improved memory, second-language learning, teaching stages, social interaction.